Expression of L protein of vesicular stomatitis virus Indiana serotype from recombinant baculovirus in insect cells: requirement of a host factor(s) for its biological activity in vitro. - Mathur, M (1996)
The 241-kDa large (L) protein of vesicular stomatitis virus (VSV) Indiana serotype, a multifunctional catalytic subunit of the viral RNA polymerase, has been expressed in Spodoptera frugiperda cells infected with recombinant baculovirus BacPAK6-L containing the L gene under the control of a polyhedrin promoter. The recombinant L protein was biologically active and supported viral mRNA synthesis in vitro. When the expressed L protein was purified by phosphocellulose column chromatography, it eluted in two peaks, one at 0.4 M NaCl (peak I) and the second at 0.75 M NaCl (peak II). The L protein in peak I showed significant transcriptional activity in an in vitro transcription reconstitution experiment, whereas the L protein in peak II was inactive. Interestingly, the addition of cytoplasmic extract from uninfected Sf21 cells to peak II completely restored transcription in vitro, indicating the requirement of a host factor(s) for the activity of the L protein. This factor is relatively heat stable and is dissociable from the recombinant L protein. It is also present in BHK, COS, and HeLa cells in detectable levels. The role of the putative host protein(s) in the activation of the L protein is discussed.